Embodiment of Smart Governance in Order to Improve the Quality of Services in Padang Panjang - Dahlan, Dewi; Putri, Indah Adi; Koeswara, Hendri; Irawati, ‎ (KnE Social Sciences, 2025)
The development of public service quality in various agencies must certainly pay attention to the satisfaction of customers or people who receive the service. The quality of public service is also related to the conditions of the product services, humans, environmental processes, where the assessment of quality is determined at the time of providing public services. When measuring the quality of service, one must refer to the customer’s expectation of the best service from the service provider. This study refers to the quality standards of service quality indicators related to five dimensions, namely: tangibles, reliability, responsiveness, assurance, and empathy. This study uses a qualitative method, namely an analysis based on data obtained through interviews and observations. The results indicate that there are several things that can be used as a formulation of public service quality in realizing smart governance in Padang Panjang City: 1. Quality of public service realizing smart governance. 2. Factors for improving the quality of public services through smart city.